2016
DOI: 10.1177/0734371x16631605
|View full text |Cite
|
Sign up to set email alerts
|

Sector Differences in the Public Service Motivation–Job Satisfaction Relationship: Exploring the Role of Organizational Characteristics

Abstract: Public service motivation (PSM) has a documented, positive effect on job satisfactionespecially in the public sector. However, organizational characteristics such as red tape, hierarchical authority, and the absence of organizational goal specificity, which are often more present in public sector organizations, may have negative influences on the PSM-job satisfaction relationship. This study explores the impact of these organizational characteristics on sector differences in the PSM-job satisfaction relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 64 publications
8
61
0
6
Order By: Relevance
“…The introduction of New Public Management (NPM) shifted the emphasis in the public sector from administration towards management in order to achieve efficiency, effectiveness and quality of care. These new business practices include new ways of managing public sector employees, and HRM was thus included in the public sector reform agenda [6]. Today the traditional notions of career service, stable and lifelong employment and service-wide employment conditions have been challenged by principles of NPM.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of New Public Management (NPM) shifted the emphasis in the public sector from administration towards management in order to achieve efficiency, effectiveness and quality of care. These new business practices include new ways of managing public sector employees, and HRM was thus included in the public sector reform agenda [6]. Today the traditional notions of career service, stable and lifelong employment and service-wide employment conditions have been challenged by principles of NPM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some P-O fit research argues that the direct effect of PSM on work attitudes is not significant, but is fully mediated by the extent to which the person-environment was fit [47,48]. Furthermore, some findings also show that the relationship between PSM and work attitudes is dependent on some organizational characteristics, such as ethical leadership, performance goal, or red tape [14,49]. Contrary to these findings, however, some results in recent years have revealed that PSM has a direct effect on the employees' work attitudes [15,9,50].…”
Section: Discussionmentioning
confidence: 99%
“…The key features of good leadership are accountability, transparency, good governance and willingness to accept valuable suggestions and comments from fellow team members and subordinates. Kjeldsen and Hansen (2018) argue that line function managers must be encouraged to adhere sufficiently to sound leadership and goverance principles, and provide aspects of good leadership and governance as accountability, objectivity, transparency, fairness and willingness to lead employees by example. Brink, Emerson and Yang (2016) and Khale (2015) has emphasised the need to comply with performance indicators stipulated in the IDP of the COT.…”
Section: Introductionmentioning
confidence: 99%